Pesticide Labeling: Protection of Pollinators - Frederick M. Fishel; James D. Ellis; Eugene McAvoy (EDIS)
On January 12, 2017 following a public comment period, the EPA announced its Policy to Mitigate the Acute Risk to Bees from Pesticide Products. This policy represents the EPA’s recommended labeling statements to mitigate acute risks to bees from pesticide products. This policy is not a regulation or an order and, therefore, does not legally compel changes to pesticide product registrations. This document outlines the highlights of the EPA policy.